2003
DOI: 10.2174/1568005033342127
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Chronic Hepatitis C: A Critical Review

Abstract: Combination therapy (Interferon plus ribavirin) is the current therapeutic gold standard for naive Hepatitis C Virus (HCV)-positive patients and with the recent advent of pegylated (PEG) IFN the rate of the sustained virological response (HCV-RNA clearance 6 months after the end of treatment) is about 54%-56% with a therapeutical gain mainly among patients with unfavourable HCV genotype (1a, 1b); in this subset of patients, a 42%-46% sustained response rate is achieved compared with 33%-36% found among genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Using this approach, the SVR is increased in approximately 50% of patients [20]. However, in the other half, HCV viremia persists and, although…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach, the SVR is increased in approximately 50% of patients [20]. However, in the other half, HCV viremia persists and, although…”
Section: Discussionmentioning
confidence: 99%
“…A frequent criticism of these trials is that the dose of standard IFN (3 MU) given in the comparator arm was too low. Although this is the FDA-approved dose in the United States, European studies performed in areas of high genotype 1b prevalence 15 show that higher doses of IFN (5-6 MU tiw or oad) obtain better results than the standard schedule. We recently performed a multicenter study involving 313 treatmentnaive patients with chronic hepatitis C genotype 1.…”
Section: Peg-ifns Plus Ribavirin: Pivotal Trials In Naïve Patientsmentioning
confidence: 98%
“…The response rate to this therapy differs among patients as the HCV genotype is a strong prognostic factor for sustained virological response (Blum, 2003;Saracco et al, 2003;Seeff and Hoofnagle, 2003). It is observed that patients with genotype 2 and 3 have a two-to three-fold higher response rate than patients infected with genotype 1 (Ghany et al, 2009;Poynard et al, 1998).…”
Section: Introductionmentioning
confidence: 99%